A patient with pulmonary hypertension waiting for donor lungs during the pandemic: 194 days on extracorporeal life support including 143 days on pulmonary artery to left atrium shunt. Issue 8 (19th January 2022) - Balik, Martin; Rulisek, Jan; Flaksa, Marek; Porizka, Michal; Mosna, Frantisek; Lindner, Jaroslav; Heller, Samuel; Belohlavek, Jan; Adla, Theodor; Schmid, Christof; Philipp, Alois; Havlin, Jan; et al.
Abstract : Patients with pulmonary hypertension and end‐stage lung disease are fraught with high mortality while on a waiting list for lung transplant. With sometimes rapid deterioration they may require veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) as an immediate life‐saving technique, which is a time‐limited solution. The technique of pulmonary artery to left atrium (PA‐LA) shunt fitted with an oxygenator enables bridging the patient to transplant for a longer time period. This low‐resistance paracorporeal pumpless lung assist device allows for de‐adaptation of the right ventricle back to lower afterload before the lung transplantation is carried out. The PA‐LA shunt with an oxygenator also conveys a risk of multiple complications with reported median of 10–26 days until transplant. We report a case of pulmonary capillary hemangiomatosis in a 35‐year‐old female who had to wait for donor lungs during the pandemic of SARS‐CoV‐2 for 143 days on PA‐LA shunt with oxygenator following 51 days on VA‐ECMO. The extremely long course associated with multiple complications including three cerebral embolisms, episodes of sepsis and ingrowth of the return cannula into the left ventricular wall gives insight into the limits of this bridging technique. Abstract : A protracted wait of greater than six months for lung transplantation on extracorporeal life support tests the limits of this bridging modality.